2004
DOI: 10.1002/dc.10419
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of CD10 in differentiating hepatocellular carcinoma from metastatic carcinoma in fine‐needle aspiration biopsy (FNAB) of the liver

Abstract: The differential diagnosis between hepatocellular carcinoma (HCC) and metastatic carcinoma, especially in moderate-poorly differentiated (MPD) HCC and poorly differentiated carcinoma, can be challenging in fine-needle aspiration biopsy (FNAB) of the liver. Recent studies demonstrate that canalicular staining for CD10 appears to be a highly specific marker for hepatocytic differentiation. The objective of this study was to test the utility of CD10 in differentiating HCC from metastatic carcinoma in FNAB of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
2
17
1
1
Order By: Relevance
“…17 However, another study, performed on formalin-fixed FNAB cell blocks, showed canalicular staining of CD10 in 82% of 22 well-to moderately differentiated HCCs. 3 The sensitivity in our cases, most of which were also well to moderately differentiated, was far lower. In addition, CD10 staining pattern was cytoplasmic and membranous in 2 HCC cases; the problem has been reported in surgical specimens as well.…”
Section: A B C D Econtrasting
confidence: 56%
See 2 more Smart Citations
“…17 However, another study, performed on formalin-fixed FNAB cell blocks, showed canalicular staining of CD10 in 82% of 22 well-to moderately differentiated HCCs. 3 The sensitivity in our cases, most of which were also well to moderately differentiated, was far lower. In addition, CD10 staining pattern was cytoplasmic and membranous in 2 HCC cases; the problem has been reported in surgical specimens as well.…”
Section: A B C D Econtrasting
confidence: 56%
“…Although the cellular features of the specimen are still essential in the differential diagnosis between HCC and MA, application of immunomarkers has improved the diagnostic accuracy and is especially helpful in challenging cases. [1][2][3] In past decades, numerous antibodies have been suggested as useful in the distinction of HCC from…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hepar1 was strongly positive, and as reported by Murakata et al, this stain has 90% sensitivity and 100% specificity for establishing the liver as the origin of a clear cell cancer [12]. Moreover, CD10 staining in a canalicular pattern, not cytoplasmic/membranous-staining pattern seen in clear cell renal cell carcinoma, further supports that this mass is hepatic in origin [13]. Finally, positive glypican 3 and diffuse sinusoidal staining pattern of CD34 further established that this was a malignant primary liver tumor [14,15].…”
Section: Clinical and Experimental Pathologysupporting
confidence: 71%
“…14,15 Polyclonal carcinoembryonic antigen and CD10 demonstrate a cannalicular-staining pattern, whilst CD34 can highlight the vessels and the endothelialised sinusoids. [14][15][16] AFP is relatively specific but lacks sensitivity being positive in less than 50% of HCC. 14,15 Hepatocyte paraffin 1 (HepPar1) is a relatively new antibody that has high sensitivity and specificity for hepatocellular differentiation.…”
Section: Discussionmentioning
confidence: 99%